The impact of elite labour migration on the identification, selection and development of European soccer players - Maguire, J.; Pearton, R. (Journal of Sports Sciences, 2000)
In this study, we examined sociocultural aspects of the identification, selection and development of elite soccer players as part of wider processes of globalization, particularly worker migration. Patterns of migration were identified among the 704 players who comprised the national squads of the 32 nations contesting the finalsof the 1998 World Cup in France.An analysis of the migration patterns within and between the six Confederations into which member nations of FIFA are grouped established the European Federation (UEFA) as soccer's core economy. The study is subsequently focused on Europe and, in particular, upon the import strategies of clubs in the four most popular destination countries - England, Germany, Italy and Spain. It is argued that, in light of European Union deregulation of worker migration between member states and, in particular, the Bosman judgement, European soccer is being reshaped. The identification and selection of elite players are producing migrant patterns that are seen increasingly to impact upon indigenous player development and, potentially, the viability and success of national teams. We argue that, although these developments are contoured in part by global economic factors, economic accounts alone do not provide an adequate understanding of them. A series of interrelated economic, political, cultural and social factors is at work. We conclude with a brief outline of the policy implications of the analysis.